Sejarah Administrasi Pidana Islam dan Relevensinya Terhadap Penanggulangan Perkara di Aceh - Said Amirulkamar; Sufrizal; M. Anzaikhan (IAIN Langsa, 2022)
As a perfect religion, the teachings of Islam clearly regulate various aspects of human life. Law enforcement and justice are a part of life that is also regulated and received attention in Islamic teachings. This includes the issue of criminal law regulated through Al-Ahkam al-Jinayah (Islamic criminal law). Speaking of Islamic Criminal Law, it is closely related to administrative affairs, for example when there are criminal cases, it requires recording, disposition, and lowering the articles against the sanctions that will be imposed. Everything goes through an administrative process that is vital in determining the outcome of the case. Departing from the above facts, this research seeks to find a correlation between the history of Islamic criminal administration and the implementation in modern-day Aceh. This research is included in the literature study with a qualitative approach, the methodology used is a descriptive analysis study. The results of the study concluded that the administration of Islamic criminal cases in Aceh is each very connected with the administrative values of the Rsulullah and Sahabat period, as for the reason because Aceh has Qanun Jinayat which makes it not rigid to positive law (General Criminal).